Cytotoxicity Effect of Bifidobacterium bifidum probiotic Cell Extract and supernatants on Adenocarcinoma gastric Cancer Cell Line and Analysis of some Apoptosis Genes Expression - Hanieh Hemmatian; Ali Sharifzadeh; Faranak Aali (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Cancer is considered one of the most significant causes of death worldwide. Probiotics are living microbes that play a significant role in protecting the host in various ways. The aim of this study was to investigate the cytotoxic effect of Bifidobacterium bifidum cell extract and supernatants as probiotic bacteria on the Adenocarcinoma gastric cancer cell line and analysis of Fas, P53, and Bcl2 gene expression. Materials & Methods: In this experimental study, the cell extract of heat-killed and supernatants Bifidobacterium bifidum was prepared. The cytotoxicity of cell extract and supernatants on AGS cell lines was evaluated in 24, 48, and 72 hours using a cytotoxicity assay. Moreover, the P53, Bcl2, and Fas apoptosis gene expression levels in the Adenocarcinoma gastric cancer cell line were analyzed using a molecular assay. The collected data were statistically analyzed using one-way ANOVA analysis with the Graph Pad Prism V.8 at the level of significance less than 0.05. Results: Supernatant (pH = 6), then supernatant (pH = 4), and then cell extracts of Bifidobacterium bifidum were able to reduce the survival rate of the AGS cell line in 48 and 72 hours. The results of gene expression by molecular method also showed an increase in Fas and P53 gene expression (p < 0.05) and a decrease in Bcl2 gene expression (p < 0.05) in the adenocarcinoma gastric cancer cell line compared to the reference GAPDH gene expression after 72 hours. Conclusion: Supernatant of Bifidobacterium bifidum with, respectively, pH = 6 and pH = 4, could induce apoptosis in the Adenocarcinoma gastric cancer cell line. So, it seems that Bifidobacterium bifidum has potential uses as a probiotic for pharmaceutical applications, including the prevention of gastric cancer.